Mediodorsal thalamic nucleus mediates resistance to ethanol through Cav3.1 T-type Ca2+ regulation of neural activity - Charles-francois V Latchoumane; Joon-Hyuk Lee; Seong-Wook Kim; Jinhyun Kim; Hee-Sup Shin (eLife)
Thalamocortical activity is known to orchestrate sensory gating and consciousness switching. The precise thalamic regions involved, or the firing patterns related to the unconsciousness, remain unclear. Interestingly, the highly -expressed thalamic T-type calcium currents have been considered as a candidate for the ionic mechanism for the generation of thalamocortically driven change in conscious state. Here, we tested the hypothesis that Cav3.1 T-type channels in the mediodorsal thalamic nucleus (MD) might control neuronal firing during unconsciousness using Cav3.1 T-type channel knockout (KO) and knockdown (KD) mice under natural sleep and ethanol-induced unconsciousness. During natural sleep, the MD neurons in KO mice showed general characteristics of sustained firing across sleep stages. We found that KO and MD-specific KD mice showed enhanced resistance to ethanol. During the ethanol-induced unconscious state, wild-type (WT) MD neurons showed a significant reduction in neuronal firing from baseline with increased burst firing, whereas Cav3.1 KO neurons showed well-sustained neural firing, within the level of wakefulness, and no burst firing. Further, 20 Hz optogenetic and electrical activation of MD neurons mimicked the ethanol resistance behavior in WT mice. These results suggest that maintaining MD neural firing at a wakeful level is sufficient to induce resistance to ethanol-induced hypnosis in WT mice. This work has important implications for the design of treatments for consciousness disorders using thalamic stimulation of deeper nuclei, including the targeting of the mediodorsal thalamic nucleus.